Colombia : Review Under the Flexible Credit Line Arrangement-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
Colombia's recovery is gaining momentum on the back of strong domestic demand, with a wider current account deficit. As a key external shock, migration flows from Venezuela accelerated in 2018 and by end-December 1.5 million migrants were estimated to live in Colombia. Risks to global growth and financial stability are tilted to the downside and have increased somewhat relative to the last FCL approval according to the April 2019 WEO and GFSR. Given the importance of oil exports and non-resident holdings of local-currency bonds, Colombia remains exposed to lower global growth, including indirectly through lower oil prices, and a sudden reversal in investor sentiment. Colombia weathered last year's financial and oil market volatility well, however, as evidenced by stable spreads and local currency bond yields.